Folate and Cancer - Luciana Yuki Tomita PhD (Journal of Inborn Errors of Metabolism and Screening, 2016)
Folate plays a central role in DNA synthesis and methylation, which are essential for DNA integrity maintenance and gene expression. Folate deficiency may lead to the incorporation of uracil into DNA and chromosome breaks, increasing the risk of cancer. However, conflicting evidence has been observed depending on the type of epidemiological study, dietary or circulating folate, and the type of cancer. New concern has arisen after a mandatory folic acid (FA) fortification program adopted for the prevention of neural tube defects in the United States, which suggested an increase in the incidence of colorectal cancer. In the present article, folate status and cancer are under review, and a discussion of the challenge of assessing folate status through food intake, supplement use, FA fortification programs, circulating folate, and the interaction of diet and the polymorphism of the enzyme involved in folate metabolism will be presented.